Symbolic Violence Teachers Experience at Schools - Süleyman Yıldız; Mithat Korumaz; Aydın Balyer (Journal of Economy Culture and Society)
The aim of this study is, first, to find out whether teachers are exposed to instances of invisible symbolic violence at school, especially in their relations with school principals, and second, if such violence exists, to expose the practices which promote it. The methodology used in this research was that of qualitative phenomenology and nine teachers were selected to take part using a snowball-sampling method, which is one of the purposeful sampling methods. In order to collect data semi structured face to face interviews were conducted. The data were analysed using a content analysis technique. As a result of the data analysis, two themes emerged: Symbolic Violence in the School Field and Struggling with Windmills. The results of the research reveal that teachers are exposed to instances of symbolic violence due to the power that principals hold within schools. Our research showed that teachers cannot cope with these practices, which produce inequality and lead to unquestioning obedience.